Clinical course of atrial fibrillation in patients who experienced coronavirus disease (COVID-19): results of a 6-month follow-up - Sychov , O.S.; Stasyshena , O.V. (Medicni Perspektivi, 2024)
Atrial fibrillation (AF) is the most common extrapulmonary complication of the past SARS-CoV-2 infection. According to experts, almost 20% of patients with past COVID-19 have a history of atrial fibrillation and the incidence of new paroxysms of this arrhythmia ranges from 10 to 18%. Referring to the studied patients who experienced COVID-19 more than 6 months ago, the subjective perception of cardiac arrhythmia is the most frequent complaint, reported by approximately two-thirds of patients. The aim of our study was to determine the course of atrial fibrillation in patients after past 2019 coronavirus disease (COVID-19) during a dynamic 6-month follow-up after the initial hospitalization for atrial fibrillation in the specialized department of cardiac arrhythmias of the SI “National Scientific Center” “M.D. Strazhesko Institute of cardiology, clinical and regenerative medicine of the National Academy of Medical Sciences of Ukraine” depending on the clinical and anamnestic, demographic, anthropometric factors, the results of laboratory research methods and the received treatment. 36 patients were included in the study, 27 of them formed the first group, which included patients in whom the course of atrial fibrillation improved against the background of recommended antiarrhythmic treatment after initial hospitalization for AF and past COVID-19, who at the time of hospitalization had a negative PCR test, of which 17 were women and 10 were men, aged 62.38±1.83 years. The second group consisted of 9 patients including 4 women and 5 men, aged 69.88±2.60 years in whom the course of atrial fibrillation neither changed nor worsened. We determined that the number of patients in whom the course of atrial fibrillation improved during the 6-month follow-up was three times greater than those in whom the course of this arrhythmia neither changed nor worsened (75% and 25%, respectively). Patients with a more favorable course of atrial fibrillation were younger (on average by 7.5 years), three times less likely to suffer from diabetes and not often had arterial hypertension of the III stage, than those examined, in whom the course of this arrhythmia did not change or worsen. Systemic inflammation and severity of heart failure significantly worsen the course of AF within 6 months after the hospital stage of treatment. However signs of deterioration of lipid metabolism are characteristic of patients with an unfavorable course of atrial fibrillation during 6 months after hospitalization, which is probably caused by the activation of systemic inflammation in them. The improvement of the prognosis of the examined patients was probably influenced by the appointment of antiarrhythmic drugs, such as: amiodarone, flecainide, beta-blockers, statins – from the "up-stream" therapy drugs.